INFLUENTIAL FACTORS AFFECTING THE DEPTH OF EXCAVATED TRENCH IN UNSATURATED SOILS DUE TO NONLINEAR SUCTION DISTRIBUTION - Man, Nguyen Xuan; Tuyet, Dao Van (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Depth of an excavated trench plays a vital role on stability as well as economic efficency of an open trench. As design and analysis excavation construction method, selection of an appropriate excavated depth value of a trench without support structures is necessary. In practice, excavated trench is usually located above ground water table or under unsaturated soil condition. Therefore, the depth of unsupported trench is significantly affected by unsaturated soil properties, especially suction distribution and physical properties of soil as well. To date, there have been a few theories and research works reported on the method of determining a suitable depth of a trench under unsaturated condition. However, previous works tend to assume that the distribution of soil suction is either constant or linear with depth; as a result of this assumption, the designed results are often overestimated compared to practical results. In this paper, the effect of nonlinear distribution of suction was taken into account to propose an equation to estimate the depth of an excavated trench without support structures. Eventually, an example of numerical computation was executed to figure out the factors that affect the depth of excavated trend considering non linear suction distribution of unsaturated soils.